2021
DOI: 10.3390/ma14112766
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Characteristics and Molecular Structure of (E)-1-(4-Chlorophenyl)-3-(4-(Dimethylamino)Phenyl)Prop-2-en-1-One (DAP)

Abstract: In this work, a laser dye of (E)-1-(4-chlorophenyl)-3-(4-(dimethylamino)phenyl)prop-2-en-1-one (DAP) was synthesized and examined as a new laser medium. The compound DAP’s photophysical properties were investigated under the influence of solvents, concentrations, and pump power excitations. The absorption spectra showed a single band, and the shape of the spectra remained the same, regardless of the optical density. The fluorescence spectra showed a band around 538 nm; its intensity was inversely proportional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…On the other hand, for the negative solvatokinetic effect, molecular conformational changes may be the main reason for increasing the values of ϕ . For alcohols solvents, such as ethanol and methanol, the ability to form hydrogen bonds between the solvent and the solute leads to fluorescence quenching owing to the deactivation of the lone pair of -N(CH 3 ) 2 [ 38 ], elucidating the low values of ϕ in these solvents.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, for the negative solvatokinetic effect, molecular conformational changes may be the main reason for increasing the values of ϕ . For alcohols solvents, such as ethanol and methanol, the ability to form hydrogen bonds between the solvent and the solute leads to fluorescence quenching owing to the deactivation of the lone pair of -N(CH 3 ) 2 [ 38 ], elucidating the low values of ϕ in these solvents.…”
Section: Resultsmentioning
confidence: 99%
“…They found that DAP exhibits dual ASE bands at 545 and 565 nm under suitable pump power laser excitation and concentration. 100 The band at 565 nm could be attributed to the combination of two excited molecules and the solvent between them (superexciplex), and it is affected by the solvent polarity, concentration and pump power energies.…”
Section: Organic Solid-state Lasersmentioning
confidence: 99%
“…[4][5][6]. While dye lasers based on rhodamine and coumarin derivatives are effective laser mediums, they have downsides, including a lack of photochemical stability [7][8][9]. To avoid these drawbacks, researchers have been making a large number of laser dyes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, during the last decade, Chalcone have received a lot of attention for their growing use in studies on the photophysical properties of organic uorescent compounds in applications such as electronic and optoelectronic devices, biological imaging, and uorescence sensors. [4][5][6]. While dye lasers based on rhodamine and coumarin derivatives are effective laser mediums, they have downsides, including a lack of photochemical stability [7][8][9].…”
Section: Introductionmentioning
confidence: 99%